A experiência da conjugalidade em casais sem filhos por opção - Santos, Andressa Nascimento dos (2022)
One of the most important choices in the life of a human being is the decision to have children. This is a well-founded concern, since it implies many changes in the lives of those who assume parenthood, as well as in the marital dynamics. An increase in the number of couples who intentionally choose not to have children is identified, considered a contemporary phenomenon, linked, among other factors, to the insertion of women in the labor market, the sexual revolution arising from contraceptive methods and investment in a professional career. Such a decision, however, requires the couple to reposition themselves in relation to investment in a romantic relationship, in individualities, in a professional career, in financial achievements, among others, in addition to dealing with possible stigmatization, prejudice or social pressure. In this way, a conjugality dissociated from parental experience and generational continuity is identified. In view of the above, the present study refers to a qualitative, descriptiveexploratory research, which aimed to understand the experience of childless couples by choice about conjugality and the motivations and desires of the choice. The study included ten childless couples who had no children from other relationships and had not undergone treatment to become pregnant. The number of participants respected the theoretical saturation sampling criterion. As instruments, a Sociodemographic Data Questionnaire and an Interview on Conjugality were used, organized and applied in a semi-structured way, with the data analyzed using Content Analysis. The results of the study were presented and discussed through two articles: “Satisfaction, cohesion and commitment: perceptions of conjugality in couples without children by choice”; and “Experiences of childless couples by choice: motivations and desires”. It was found that for these couples, there was never a reason to have children, desire and choice were never part of their lives. Regarding the marital experience, in a broad way, couples reported high levels of marital satisfaction and commitment, resulting in an increase in cohesion between partners. The results show a perception on the part of couples of quality and equality in the relationship, investment in leisure, freedom, and professional life. Regarding social expectations, although the choice not to have children was portrayed as more socially accepted, couples still indicated the prejudice and stigma related to the choice.